ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT JUDGMENT PADA AUDITOR - Limen, Michelle Meivina Putry; Karamoy, Herman; Gamaliel, Hendrik (JURNAL RISET AKUNTANSI GOING CONCERN, 2017)
Audit Judgment is auditorâs policy in giving an opinion on the information found along the audit process, which refers to an idea, a notion or an estimation about events that happened on the audit object. The outcome that is issued by an auditor has to be able to provide the right information and evidence thus the delivered audit judgment will be correct or will fit. Therefore, itâs important to know which factors are able to influence the audit judgment. This research aims to empirically test the influence of the pressure of obedience, task complexity and audit experience on the quality of audit judgment. Research was held on two objects, which were Ariesman Auly Public Accounting Firm Manado and Badan Pengawas Keuangan dan Pembangunan (BPKP) Provinsi Sulawesi Utara. Total of obtained samples were 30 auditors. The used sampling method was Ordinal Regression Analysis. The result of this research shows that the pressure of obedience influences audit judgment significantly, while task complexity and audit experience do not have significant influence on audit judgment.Keywords : pressure of obedience, task complexity, auditing experience, audit judgment, ordinal regression analysis